An Eigenvalue Study on the Variant of Murali-Lakshmanan-Chua Circuit - and B.V.Bhuvaneswari, G.Sivaganesh M.Daniel Sweetlin (Recent Research in Science and Technology, 2015)
In this paper, the eigenvalues of a simple second-order non autonomous chaotic circuit namely, the variant of the Murali-Lakshmanan-Chua’s (MLCV) circuit is studied. The dynamical behaviour of the circuit is obtained by means of a study on the Eigen values of the linearized Jacobian of the nonlinear differential equations. The trajectories of the Eigen values as functions of the dynamic parallel loss conductance explaining the supercritical hopf bifurcation exhibited by the autonomous system is presented.